Выражение “временного состояния” как разновидность непроцессного именного сказуемого - Драздаускас, А. (Kalbotyra, 1971)
The article deals with the problem of interaction between colligation and collocation on the basis of non-process nominal predicate in Modem English.The investigation is confined to the analysis of one type of non-process nominal predicate which serves as a linguistic expression of state. Detailed semantic analysis of the predicative of this particular type of predicate has been undertaken and 4 main groups of words and word-combinations in the function of predicative have been established. They are: 1) words of the category of state, 2) adjectives and participles II, 3) prepositional adverbs, 4) prepositional phrases.We have proposed the term “the predicate of state” for this particular type of non-process nominal predicate and we assume that syntactic categorization is greatly determined by collocation, i.e. lexico-phraseological combinability of words.